Pengaruh Big 4 Auditor Utilization, Audit Committee, dan Capital Intensity terhadap Tax Aggressiveness - Nasywa Thania; Abdillah Arif Nasution; Adi Syah Putra; Dio Agung Herubawa (Lembaga Yasin AlSys, 2026)
Although tax aggressiveness has been widely examined in the taxation and corporate governance literature, research findings on the effects of Big 4 Auditor Utilization, Audit Committee, and Capital Intensity on Tax Aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange remain inconsistent. This study aims to analyze the effects of Big 4 Auditor Utilization, Audit Committee, and Capital Intensity on Tax Aggressiveness in manufacturing sector companies listed on the IDX during the 2021–2024 period. This study used a causal quantitative approach with a population consisting of manufacturing sector companies listed on the IDX during the study period. The sample was determined using purposive sampling, resulting in 58 companies with a total of 232 observation data. The data were analyzed using multiple linear regression for panel data with the Fixed Effect Model (FEM) selected, accompanied by classical assumption tests and hypothesis testing using EViews 12 software. The results showed that Audit Committee had a significant negative effect on Tax Aggressiveness, whereas Capital Intensity had a significant positive effect on Tax Aggressiveness. Meanwhile, Big 4 Auditor Utilization had a positive but insignificant effect on Tax Aggressiveness. These findings contribute to the development of the literature on the determinants of tax aggressiveness, particularly in the context of manufacturing companies in Indonesia. Practically, the results of this study may serve as a consideration for management and regulators in strengthening corporate governance mechanisms and formulating more accountable tax strategies.